Development of Students’ Workbook with STEAM-Real World Problem to Improve Middle School Students’ Problem-Solving Skills on Temperature and Heat Material - CAHYANINGTYAS, Aprilia; PHANG, Fatin Aliah; YULIANTI, Erni (Journal of Research in Educational Sciences, 2025)
Problem-solving skills are essential for students to face the challenges of the 21st century. However, based on observations and PISA 2022 data, junior high school students in Indonesia still have low problem-solving skills. The learning media used in the learning process is still conventional, still does not support problem-solving skills. This study aims to develop learning media in the form of students' workbooks with STEAM-Real World Problem content to improve students' problem-solving skills in temperature and heat material. The development followed the 4D model (Define, Design, Develop, Disseminate). The product was validated by 2 media and material experts, and readability was tested by 2 science teachers and 10 students. A total of 8 pretest and posttest questions covering problem-solving indicators were tested for validity and reliability, with valid results and a Cronbach's Alpha value of 0.665 (reliable). The empirical test involved 26 grade VII students. The effectiveness test used a quasi-experimental design with a non-equivalent control group model in two classes (28 students each). Results showed significant improvement, with an N-Gain of 61.81%. The “implementing the plan” indicator showed the highest increase, from an average score 8.81 (pretest) to a score of 68.19 (posttest). This improvement was supported by workbook activities such as designing a simple cooler, creating a poster, and calculating heat. These activities can provide space for students through experiments, visualization, creativity, and mathematical calculations. Thus, the students' workbook developed has valid, reliable, and effective criteria in improving students' problem-solving skills.